A STUDY OF THE IMPACT OF GLOBALIZATION ON THE WOMEN IN THE HIGHER EDUCATION - Goyal, Anita (International Journal of Multidisciplinary Research and Studies, 2020)
According to the findings of the study, factors such as household wealth and women's educational status have a significant bearing on the number of female farmers who are employed. This is reinforced by the fact that there is a negative connection between socioeconomic qualities and the respondents' engagement in crop production. The respondents' involvement in crop production decreases as socioeconomic features increase. The percentage of women who work in dairy farming ranges from 45 to 70 percent. In rural regions, women are responsible for practically all of the duties associated with the dairy industry There is no denying the contribution that Indian women have made to their nation's development; nonetheless, the level of their involvement varies considerably throughout time and space. The considerable role that women play in agriculture, jobs closely connected to it, and domestic responsibilities have been largely ignored. The ever increasing demand for milk and other dairy products has turned dairy farming into a lucrative industry for women The Indian government reports that 85 percent of rural women are involved in the cattle industry. The phrase "globalization" has become synonymous with this decade. It is a phrase that has become so ubiquitous that it may be found in every aspect of society. It is not simple to determine (Burbules et al. 2000) what is at stake in the globalization question, the functions that the word truly performs, and its repercussions for modern theory, policy, and critical pedagogy.